Annulment of Land Rights Certificate Due to Unlawful Act: Analysis of Supreme Decision 172 PK/Pdt/2023 - Jerry Shalmont; Felicia Angeline Angeline; Marsha Carolina Wijaya Wijaya (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
Land title certificates in Indonesia serve as strong evidence of ownership, yet their validity is relative rather than absolute and may be annulled if issuance originates from an unlawful act. This study aims to analyze the legal basis for annulling land certificates predicated upon tortious conduct and to assess the implications of such judicial action for the protection of legitimate rights holders. Employing a normative juridical method with statutory, conceptual, and case-law approaches, this research examines the Supreme Court's jurisprudence in annulling a certificate issued through an unlawful act. The findings reveal that the unlawful acts doctrine, as codified in the civil code, operates as an effective corrective mechanism against maladministration in land registration, enabling civil courts to invalidate state-issued certificates tainted by tortious conduct. The study further demonstrates that the decision reinforces the primacy of substantive justice over formal legal certainty, thereby strengthening legal protection for rightful landowners and promoting integrity within the national land administration system. This research contributes to the development of Indonesian agrarian law by clarifying the jurisprudential basis for certificate annulment and its systemic implications.